The Use of Cooperative Learning Strategy to Improve Student’s Reading Skill - Hirma Mutiara Suyeti; Syarifuddin Dollah; Andi Anto Patak (International Journal of Language, Education, and Literature, 2025)
This research aims to determine the effectiveness of using a cooperative learning strategy to improve student’s reading skills in learning using the cooperative strategy. The research data were qualitative. The research subject was 23 students. It comprises 12 female and 11 male students of the English Language Faculty at UNM Makassar.In the academic year 2023/2024. The research data was gathered through monitoring the teaching-learning process, interviewing students and collaborators, talking with collaborators, and photographing the learning process. The action research was carried out in two cycles, with cooperative learning methods such as pair-reading, think-pair-share, numbered head together, round table brainstorming, and group discussion as the main activities, with various ready tasks, engaging media, material handouts, and rewards serving as complements. The instruments employed in this study were observation guidelines, interview guidelines, and digital cameras. The results demonstrate that cooperative learning increased students' reading skills in various areas, such as finding significant concepts, obtaining essential information, and guessing. Students appeared more eager and engaged in the teaching and learning process. Keywords: Cooperative Learning Strategy, Reading Skill, Reading Comprehension